THE EVOLUTION OF USER INTERFACE COMPONENTS IN WEB DEVELOPMENT - Karthik Vallamsetla (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article traces the evolution of user interface components in web development, from the early days of static HTML elements to modern component-based architectures. It explores how this shift has revolutionized web development practices, enhancing code reusability, maintainability, and scalability. The article examines the limitations of static HTML, the rise of component-based architecture, and the impact of modern frameworks like React and Angular. Through case studies of Airbnb and Spotify, it illustrates the real-world benefits of component-based development. The article also discusses the numerous advantages of this approach, including improved development speed, enhanced collaboration, better performance, easier testing, and long-term benefits. By analyzing this evolution, the article provides insights into current web development trends and potential future directions in UI component architecture.